The Tollet system and the pavilion as an archetype of the first modern hospital in Mexico - Córdoba Flores, Consuelo (2022)
Hygienism as a current of thought permeated the health sciences and policies of governments, spreading its influence not only in Europe, but also in the world. In the discipline of architecture, hygienist precepts were embodied in the archetype of the "model hospital", inspiring the design of new construction systems, such as the Tollet system, distinguished by the construction of pavilions with pointed vaults, whose shape, in relation to with the precise arrangement of large windows and different openings that would promote, through natural ventilation, the effective evacuation of malignant effluvia, known at that time as miasmas. This work analyzes the vicissitudes that had to be resolved during the construction of the General Hospital of Mexico, in an attempt to capture the hygienist maxims of the modern french "model hospital" and the Tollet system, whose solution finally led to the construction of wedge vaults. of thin brick, designed by Rafael Guastavino.